Solving transcendental equation using genetic algorithm / Masitah Hambari - Masitah , Hambari (2004)
A problem of great importance in engineering is finding the roots of the equations. There are closed form expressions for the case of linear, quadratic or cubic equations. For higher orders like Transcendental Equation, Numerical Methods is used to find the solutions. Genetic algorithm (GA) has long been used for optimization problems that arise in a wide variety of complex systems. This project studies and explores the potential of using Genetic Algorithm to solve Transcendental Equation. Genetic Algorithm is used to find the roots or set of optimal solution that satisfy the equation. The most critical task for developing this project is how to encode the algorithm based on the domain, Transcendental Equation. This project studies the potential of using Genetic Algorithm and develops a program in order to solve Transcendental Equation in optimizing problem domain. This solution hopefully may provide a potential alternative for a better solution.